(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
Purpose: This study aims to conduct a comprehensive scientific mapping of the relationship between agricultural subsidies and farmers by synthesizing literature across disciplines such as economics, social sciences, finance, business, and management. The primary objective is to identify research gaps and provide a detailed analysis of trends, key contributors, and future research directions in the field of agricultural subsidies. Methodology: A bibliometric analysis was performed on a dataset of 903 documents related to agricultural subsidies and farmers, covering the years 2003 to 2023. The data was extracted from the Scopus database and analyzed using VOSviewer and R-Studio to streamline the results generation process. Findings: The study analyzes data from leading agricultural-producing nations, various journals, diverse sources, authors, academic institutions, and highly cited publications. It reveals key contributors and identifies trends in agricultural subsidies research. The dataset spans 2003 to 2023 and comprises 903 research papers focused on the impact of agricultural subsidies on farmers.